Method for identifying aging behavior of cultural relic protection material and researching interaction between cultural relic and protection material

Through fluorescent probe recognition and three-dimensional fluorescence imaging technology, the problem of difficult identification of aging behavior of polymer protection materials on cultural relics surfaces is solved, and high sensitivity research on the interface between polymers and cultural relics is realized. The impact of polymer aging on cultural relics is explored. Cultural relics protection provides new ways.

CN119413764APending Publication Date: 2025-02-11BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410064357.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively identify and study the aging behavior of polymer protective materials on the surface of cultural relics and their impact on the body of cultural relics. Traditional methods cannot provide interface information between polymer and cultural relics matrix, which limits the study of the interaction between cultural relics and protective materials.

Method used

The fluorescent probe recognition method is used to target the functional groups generated by polymer aging, and visualize the interface between the polymer and the cultural relics through three-dimensional fluorescence imaging, and combine various research methods to explore the aging process of polymer coatings for cultural relics. The act of damage to the ontology.

Benefits of technology

A high sensitivity study on the aging behavior of polymer sealing layers has been achieved, and the interaction between cultural relics and polymers has been explored, providing new methods and understandings for cultural relics protection and material optimization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004667587080000011
    Figure HDA0004667587080000011
  • Figure HDA0004667587080000012
    Figure HDA0004667587080000012
  • Figure HDA0004667587080000013
    Figure HDA0004667587080000013
Patent Text Reader

Abstract

The invention discloses a method for identifying aging behaviors of a cultural relic protection material and researching interaction between a cultural relic and the protection material, and belongs to the technical field of cultural relic protection analysis. Targeted recognition is performed on different functional groups generated by aging of a cultural relic sealing and protecting polymer based on a fluorescent probe, visualization of an interface between the polymer and a cultural relic body is realized through a three-dimensional fluorescent imaging method, and the influence of the cultural relic on the aging process of the polymer is explored through quantitative analysis by adopting a control experiment. By combining a traditional Fourier transform infrared spectrometer, a gel permeation chromatography, an X-ray electron spectrometer and the like, the aging behavior of the polymer and the cultural relic body are researched, and the influence of the aged cultural relic body on the polymer and the influence of the polymer on the cultural relic body are verified. According to the method, the aging behavior research on the metal-polymer interface is realized through a high-sensitivity three-dimensional imaging method, the influence behaviors of the polymer on cultural relics and the influence behaviors of the cultural relics on the polymer are explored, and a new method and cognition are provided for cultural relic protection and material optimization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cultural relic protection and analysis, and specifically relates to a fluorescent identification method for the aging behavior of polymer protective materials on the surface of cultural relics, and a research method for the interaction between cultural relics and their protective materials. The invention not only studies the influence of cultural relics on polymer protective materials, but also studies the influence of aging of protective materials on the cultural relics themselves, and can select different protective materials for different cultural relics. Background Art

[0002] After a long period of baptism, the cultural relics themselves are very fragile and easily damaged by physical, chemical and biological effects, making them difficult to preserve. It is particularly important to take measures to protect the surface of cultural relics. The surface protection of cultural relics is to apply protective materials on the surface of cultural relics by spraying or brushing, that is, to form a protective film to block the influence of pollutants such as oxygen, moisture and particulate matter in the external environment to achieve the effect of protecting cultural relics. With the development of science and technology, more and more organic polymers are widely used in the field of cultural relics protection, such as acrylic resins (B72, B66, etc.), polyurethane and epoxy resins, which have the advantages of excellent ductility, fast film formation and fast adhesion, but also have disadvantages such as easy aging. Therefore, in order to better protect cultural relics, it is of great significance to identify the aging behavior of cultural relic protection materials and understand the interaction between cultural relic protection materials and cultural relics.

[0003] In the study of the aging of cultural relic protection materials, most of the focus is on exploring the chemical structure changes and macroscopic performance changes (such as water contact angle, tension, etc.) caused by external stimuli of organic polymers themselves, and less attention is paid to the mutual influence between the cultural relic matrix and the protective material. However, there is also an interaction between cultural relics and polymer coatings. On the one hand, cultural relics will affect the aging process of polymer coatings; on the other hand, the aging of polymer coatings on the surface of cultural relics not only affects the protection of cultural relics due to yellowing and cracking, but also produces harmful substances that cause secondary damage to the cultural relics. In addition, traditional studies on the aging behavior of organic polymer materials often use methods such as thermogravimetric, infrared, and size exclusion chromatography. Although they can provide degradation information for the polymer itself, they cannot provide interface information between the polymer and the cultural relic matrix, which limits the study of the interaction between the cultural relic matrix and the polymer sealing material. Therefore, there is an urgent need for a detection method for the aging of cultural relic surface sealing materials, which can not only detect the aging behavior of cultural relics with high sensitivity, but also analyze the interface changes between cultural relics and polymers, so as to realize the exploration of the interaction between cultural relic surface sealing materials and cultural relic matrix.

[0004] The method of the present invention is based on the targeted identification of different functional groups produced by the cultural relic sealing polymer due to aging by fluorescent probes, and realizes the visualization of the interface between the polymer and the cultural relic body through the method of three-dimensional fluorescence imaging; and can perform three-dimensional imaging quantitative research on the volume, growth depth and other information of the fluorescent signal points at different positions, and analyze the mechanism of the influence of the cultural relic body material on the polymer aging behavior during the polymer aging process. Further combined with a variety of research methods, the damage behavior of the polymer coating aging process to the cultural relic body is explored. This method is safe, rapid and non-destructive, and realizes the study of the aging behavior of the polymer sealing layer, explores the interaction between cultural relics and polymers, and provides new methods and understandings for cultural relic protection and material optimization. Summary of the invention

[0005] The present invention provides a method for identifying and fluorescently analyzing the aging behavior of a cultural relic sealing coating, and explores the mutual influence between the metal cultural relic body and the sealing polymer.

[0006] The technical solution of the present invention is to test and study the cultural relic samples with polymer coatings. First, a specific fluorescent dye is selected, and a fluorescent probe recognition method is used to perform targeted recognition and staining on the functional groups generated by polymer aging; a three-dimensional imaging analysis of the aging sites generated by the polymer is performed by laser scanning confocal microscopy, and attention should be paid to both the surface of the polymer material and the interface between the polymer and the cultural relic. A control experiment and quantitative analysis are used to explore the influence of cultural relics on the aging process of the polymer. Second, the aging behavior of the polymer is verified by Fourier transform infrared spectrometer, gel permeation chromatography, etc., and the influence of cultural relics on it is explored. Third, the body of the cultural relic with the protective layer removed is studied by X-ray electron spectrometer, electrochemical test and other methods to explore whether the aging polymer has an impact on the body of the cultural relic. Based on this, on the one hand, the influence of the cultural relic body on the aging process of the polymer through the interface is analyzed, and on the other hand, the secondary damage caused by polymer aging to the body of the cultural relic is studied. This method realizes the study of the aging behavior of the metal-polymer interface through a highly sensitive three-dimensional imaging method, explores the influence of polymers on cultural relics and cultural relics on polymers, and provides new methods and understandings for cultural relic protection and material optimization.

[0007] A research method for identifying the aging behavior of cultural relic protection materials and the interaction between cultural relics and protection materials, characterized by comprising the following steps:

[0008] (1) Preparation of polymer coating

[0009] The polymer is coated on the antique metal surface by spin coating, drop coating, solvent evaporation and the like. The thickness can be adjusted by changing the concentration and amount of the polymer.

[0010] (2) Polymer coating aging test

[0011] The antique metal with the polymer coating sealed in step (1) is placed in a weather aging test chamber for accelerated aging treatment; the temperature range for thermal aging is 20-400°C, the wavelength of the ultraviolet light aging is 280-400nm, and the irradiation power is 0.05-2.00W / m 2 / nm, the aging treatment time is 0-10 days, and the polymer material is aged for different time periods;

[0012] (3) Fluorescent labeling of aged polymer coatings

[0013] The polymer coating undergoes an aging reaction, undergoing chemical changes to produce different functional groups; based on the different groups produced by the aging of the polymer coating, select specific fluorescent probe molecules corresponding to each group. For example, acrylic resin B72 produces carboxyl groups upon aging, and 6-aminofluorescein (AF) fluorescent molecules need to be selected to perform specific fluorescent recognition of the carboxyl groups to achieve staining; select a stain based on the functional groups that may be produced by the aging of the polymer coating in step (2), immerse the antique metal in the fluorescent stain for 30 minutes, so that the functional groups produced by aging are stained by the fluorescent probe molecules, and then rinse with deionized water for 1 minute to wash away the free fluorescent probe molecules, and fix the stained sample on the sample stage for confocal three-dimensional fluorescence imaging;

[0014] (4) Fluorescence imaging and quantitative analysis of cultural relics sealed with polymers

[0015] A laser scanning confocal microscope is used to observe and image the polymer of the dyed sealing cultural relics or antique metal: different lasers (such as 405nm, 488nm and 552nm, etc.) are used to excite different probe molecules in the polymer in step (3), and the emission wavelength range is adjusted to capture the emission wavelength signals of different fluorescent molecules for imaging. For example, the acceptance range of 430-470nm accepts blue light, the acceptance range of 510-560nm accepts green light, the acceptance range of 570-600nm accepts orange light, and the acceptance range of 620-650nm accepts red light. The scanning range of the Z axis is appropriately adjusted according to the thickness of the polymer sealing layer. For example, if the thickness of the polymer sealing layer is 10-200μm, the Z axis range should also be set to 10-200μm, and the step size can also be adjusted between 0.1-2μm.

[0016] Quantitative information is obtained through the results of three-dimensional imaging for analysis, and the aging sites on the polymer surface and the polymer-artifact interface are studied. The aging behavior at the polymer-artifact interface is explored through analysis and comparison of the depth and volume changes of the fluorescence sites, and the influence of the artifacts at the interface on the aging of the polymer is analyzed;

[0017] At the same time, control experiments and quantitative analysis were used to explore the impact of cultural relics on the aging process of polymers.

[0018] (5) Comparative study of cultural relics sealed with polymer and inactive substrates

[0019] Select inactive substrates such as quartz wafers and silicon wafers as control samples to replace antique metals, and use the same spin coating, aging treatment, fluorescent staining, imaging and quantitative analysis methods to compare the effects of inactive substrates and antique metals on the aging process of polymers; use fluorescent imaging analysis and other methods to compare the influence of different substrates, such as using the same method as step (4) to compare the aging points on the polymer upper surface and the interface with the substrate corresponding to different substrates. The aging points on the polymer upper surface corresponding to the inactive substrate and the polymer upper surface corresponding to the antique metal have the same growth trend or little difference. At the same time, if the growth trend of the aging sites on the surface of the inactive substrate is more or larger than the growth sites on the surface of the antique metal, it is possible that the antique metal has an effect on the aging process of the polymer; age the polymer coatings on different substrates for different times and test the infrared spectrum, perform spectrum analysis, calculate the carbonyl index, etc., to compare the effects of different substrates on the aging process of the polymer, so as to explore and then obtain whether the antique metal accelerates or inhibits the aging process of the polymer protective layer;

[0020] (6) Study the chemical changes of the cultural relics themselves, and then explore whether the substances produced by the aged polymers will affect the cultural relics themselves

[0021] (a) Subjecting cultural relics or antique metals that have been sealed with polymer coatings to aging treatments for different periods of time, including sealing with the polymer coatings but without aging and aging for a period of time, and then removing the polymer with a solvent, and performing X-ray electron energy spectrum and metal electrochemical tests on the newly exposed surface of the cultural relics; (b) Subjecting cultural relics or antique metals that have not been sealed with polymer coatings to aging treatments under the same conditions as step (a), combining step (a) to explore whether the substances produced by the aged polymer will have an impact on the cultural relics themselves.

[0022] Taking X-ray electron spectroscopy analysis as an example, the ratio of the active substances newly generated by aging to the inactive substances in the body of the cultural relics is: Fe 3+ (Represents active substances newly generated due to aging) / Fe 0 (representing the inactive substance content of the cultural relic itself) to quantitatively analyze the impact of aging polymer on the cultural relic itself. 3+ / Fe 0 The ratio of Fe to unsealed polymer-coated cultural relics after aging under the same conditions 3+ / Fe 0 The ratio of > unaged cultural relics Fe 3+ / Fe 0The ratio of polymer to cultural relics shows that aging of polymer has an impact on the cultural relics and caused damage to them.

[0023] Exploring the impact of cultural relic polymers on the cultural relic itself is a necessary aspect of protecting cultural relics and avoiding secondary damage to cultural relics. By studying the impact of different polymer materials on the cultural relic itself, we can screen out polymer protective materials that are less harmful to cultural relics and can safely protect cultural relics (such as the material that has an inhibitory effect on the aging process of the polymer sealing layer in step 5, and the material that the substances produced by the aged polymer in step (6) will not affect the cultural relic itself), so as to achieve long-term and safe protection of cultural relics. The impact of the cultural relic itself on the polymer directly determines the protective effect and service life of the polymer; exploring the impact of the cultural relic itself on the polymer is conducive to understanding the service life of the polymer, replacing or repairing the polymer protective material before it fails, and avoiding the damage of the cultural relic due to the failure of the protective material, which causes it to lose its protective effect on the cultural relic itself.

[0024] The present invention provides a non-destructive, three-dimensional, quantitative analysis method to detect the aging of polymer coatings on the surfaces of metal cultural relics. Based on the obtained results, it can be analyzed whether the material of the cultural relic body promotes or inhibits the aging of the polymer during the aging process of the polymer. It can also be analyzed whether the aging process of the polymer coating causes damage to the cultural relic body. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 They are respectively the fluorescent three-dimensional imaging images of the antique cast iron surface sealing coating B72 after photothermal aging for 0h, 6h, 24h and 30h (excitation wavelength is 488nm, emission collection range is 515-565nm).

[0026] Figure 2 Schematic diagram of the volume measurement of aging fluorescence points at the interface. A is the aging fluorescence at the interface of antique cast iron and surface sealing layer B72.

[0027] Schematic diagram of point volume measurement, B is the fluorescence point volume change diagram of fluorescence three-dimensional imaging of antique cast iron surface polymer coating B72 after photothermal aging at different times.

[0028] Figure 3 This is the side view of fluorescence three-dimensional imaging of the polymer coating B72 on the antique cast iron surface and quartz glass surface after 6 hours of photothermal aging.

[0030] Figure 4 The infrared spectra of the comparison sample B72: from top to bottom are B72 on the antique cast iron surface after photothermal aging for 30 hours, B72 on the quartz glass surface after photothermal aging for 30 hours, and unaged B72.

[0031] Figure 5This is the X-ray electron energy spectrum of Fe2p on the surface of antique cast iron: A is the bare iron surface after photothermal aging for 30 hours, B is the cast iron surface after coating B72, photothermal aging for 30 hours and removal of the coating, and C is the cast iron surface after coating B72 without photothermal aging and removal of the coating.

[0032] Figure 6 Polarization curves of antique cast iron surface sealing coating B72 after 0 days (solid line) and 10 days (dashed line) of light-heat aging

[0033] Test picture. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0035] Embodiment 1:

[0036] (1) B72 sealant on antique cast iron surface

[0037] For antique cast iron, before surface sealing, its (10mm×10mm×1mm) surface needs to be cleaned. First, the gray cast iron surface is cleaned with detergent, and polished with sandpaper of 600, 1500 and 8000 grit, respectively. Then, the cast iron surface is cleaned with acetone to ensure the cleanliness of the cast iron surface. The film is prepared on the cast iron surface by spin coating. The acrylic resin B72 with a mass fraction of 10% is spin coated on the cast iron surface. The speed of the coating machine is set at 3300r / min, and the spin coating time is set to 6s.

[0038] (2) Photothermal aging of antique cast iron for sealing B72

[0039] The antique cast iron sealed with B72 was placed in the Q-Lab QUV UV / spray accelerated weathering equipment for accelerated photothermal aging treatment. The temperature was set to 60°C, the UV wavelength was 340nm, and the irradiation power was 1W / m 2 , sampling was carried out every 3 hours.

[0040] (3) Preparation of fluorescent dyeing solution and fluorescent marking of antique cast iron with B72 seal

[0041] 6-Aminofluorescein (AF) was dissolved in dimethyl sulfoxide (DMSO) at a concentration of 10 mmol / L, and then the stock solution of AF was diluted to 0.12 mmol / L using 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (1 mmol / L), N-hydroxysuccinimide (1 mmol / L) and a buffer solution at pH = 5 to finally obtain a fluorescent staining solution that can stain the carboxyl groups generated during the aging process of the polymer.

[0042] The antique cast iron after photothermal aging treatment was immersed in a fluorescent dye solution (about 5 mL of AF dye was used for one experimental sample) for 30 minutes to achieve sufficient fluorescent labeling. The antique cast iron was then rinsed with deionized water (1 min) to remove free dye molecules. Finally, the antique cast iron of seal B72 was fixed on the sample stage for fluorescence imaging. (4) Fluorescence imaging and quantitative analysis of antique cast iron of seal B72

[0043] Laser scanning confocal fluorescence microscopy was used to capture the fluorescence changes of B72 staining on the antique cast iron surface. The excitation wavelength was set to 488nm, and the fluorescence emission was collected in the range of 515-565nm. The range of the X-axis and Y-axis was 1.16mm, the depth of the Z-axis was set to 15μm according to the film thickness of B72, and the step size was set to 0.1μm. Three-dimensional fluorescence imaging was performed under these conditions.

[0044] like Figure 1 As shown in A, the B72-sealed cast iron has no fluorescent signal after being stained before aging, but after aging for 6 hours ( Figure 1 After aging, obvious fluorescent spots appeared. As the aging time increases, the number of fluorescent spots increases ( Figure 1 In addition, it is worth noting that the depth of the fluorescent spot is deep and can penetrate the entire B72 film, indicating that a large number of carboxyl groups are generated in B72.

[0045] The volume changes of the fluorescent spots after aging and staining of the B72-sealed cast iron were further statistically analyzed. The results show that the total fluorescent volume within the imaging field of view increases with the aging time, from 0 μm at the initial 0 h to 1.5 μm at the initial 0 h. 3 After aging for 30 hours, it increased to 3159 μm 3 The volume changes of the fluorescent spots from the B72 surface to the B72-cast iron interface (from top) and from the B72-cast iron interface to the B72 surface (from bottom) were further statistically analyzed. From the statistical values, the volume of the fluorescent spots growing from the interface between the antique cast iron and B72 (1735μm 3 , 30h) is larger than the volume of the fluorescent dots grown from the B72 surface (1424μm 3 , 30h). The above results prove that cast iron affects the aging reaction process of B72, accelerates the aging degradation of B72, and produces more carboxyl substances. Not only does it shorten the service life of B72, but these active substances may further react and affect the properties of cast iron itself.

[0046] (5) Comparative study of antique cast iron and quartz glass for sealing B72

[0047] As a reference, B72 was also coated on quartz glass (10mm×10mm×1mm) by spin coating. The quartz glass was first cleaned with detergent and then ultrasonically treated in acetone for 2 minutes. The polymer coating B72 was spin coated at 3300r / min for 6s using a sizing machine to coat B72 on the quartz glass. The aging and stain imaging analysis process of the quartz plate sealed with B72 was consistent with that on the antique cast iron.

[0048] From the fluorescence three-dimensional imaging cross-sectional diagram, it can be seen that there are significant differences in the growth of aging sites on the antique cast iron surface B72 and the quartz glass surface B72: for the antique cast iron, there are fluorescent spots growing on the upper surface of B72 and on the side of the B72-cast iron interface ( Figure 3 A in the middle); for quartz glass, only the fluorescent spots growing from the upper surface of B72 ( Figure 3 The above results prove that quartz glass does not affect the aging process of B72, while antique cast iron has an effect on the aging process of B72 at the interface.

[0049] Infrared spectrum test was performed on antique cast iron and quartz glass sealed with B72. Antique cast iron and quartz glass samples aged for 30 hours and blank samples aged for 0 hours were selected for sample preparation and testing. First, acetone was used to dissolve the B72 on the surface of the sample, and then the solution was dripped onto the potassium bromide tablet. After the acetone was completely evaporated, the infrared test could be performed. The test wavelength range was 4000-400cm -1 The infrared spectra of the B72 film on cast iron and the B72 film on quartz after aging are located at 1729cm -1 The absorption peak attributed to carbonyl group increased significantly compared with the blank sample ( Figure 4 ). Carbonyl index of blank sample, quartz glass surface B72 after 30 hours of light-heat aging, and antique cast iron surface B72 after 30 hours of light-heat aging The values ​​are 2.85, 3.02 and 4.23 respectively, which further proves that the presence of antique cast iron accelerates the aging process of B72. (6) Study on the chemical changes of antique cast iron itself

[0050] The antique cast iron sealed with B72 was removed with acetone after 0 hour and 30 hours of photothermal aging, and the exposed cast iron surface was tested by X-ray electron energy spectrum, and Fe2p was analyzed. Figure 5 A in the figure is bare iron subjected to 30 hours of light-heat aging. Figure 5 B in the figure is the antique cast iron surface after the cast iron was coated with B72 and the surface protective layer was removed after 30 hours of light and heat aging. Figure 5 C in the middle is the antique cast iron surface of the cast iron coated with B72 without aging and removing the surface protective layer. The part filled with vertical stripes in the figure represents Fe3+ , the horizontal stripe shaded area represents Fe 0 As can be seen from the figure, the surface of the cast iron aged for 0 hours is mainly composed of zero-valent Fe, while the content of Fe ions on the surface of bare iron and B72-coated cast iron after aging for 30 hours increases significantly. 3+ / Fe 0 The ratio of Fe and Fe on the surface of bare iron and cast iron coated with B72 after 30 hours of light-heat aging was quantitatively calculated. 3+ / Fe 0 The ratios of B72 and B72 were 2.32 and 4.55, respectively, indicating that the coating of B72 and then aging increased the Fe content in cast iron. 3+ As a control, the Fe content of the surface of the antique cast iron coated with B72 without light and heat aging was 3+ / Fe 0 The above results show that cast iron with B72 seal will produce more Fe than bare iron without seal. 3+ This is because the aging of B72 will produce a large number of carboxyl groups, which further aggravates the corrosion of Fe and has a deteriorating effect on the protected cultural relics.

[0051] Polarization curves of sealed B72 antique cast iron after photothermal aging for 0 days and 10 days were further measured. The electrochemical experiment used a three-electrode system consisting of a silver / silver chloride reference electrode, a platinum counter electrode and an antique cast iron working electrode, and the electrolyte was sodium sulfate (0.2 mol / L). Figure 6 As shown in the figure, the polarization curves of the antique cast iron sealed with B72 after 0 and 10 days of photothermal aging are shown. The corrosion current density is calculated by Tafel extrapolation method, and the results show that the corrosion current density of the antique cast iron surface after 0 and 10 days of photothermal aging is 1.332×10 -5 A.cm 2 and 3.601×10 -5 A.cm 2 The above results show that aged B72 produces corrosive substances, which affect the cast iron itself.

Claims

1. A research method for identifying the aging behavior of cultural relics protection materials and the interaction between cultural relics and protection materials, characterized in that: The following steps are involved: (1) Preparation of polymer coating The polymer is coated on the antique metal surface by spin coating, drop coating, solvent evaporation and the like. The thickness can be adjusted by changing the concentration and amount of the polymer. (2) Polymer coating aging test The antique metal with the polymer coating sealed in step (1) is placed in a weathering test chamber for accelerated aging treatment. The temperature range for thermal aging is 20-400°C, the wavelength of the ultraviolet light for light aging is 280-400nm, and the irradiation power is 0.05-2.00W / m 2 / nm, the aging treatment time is 0-10 days, and the polymer material is aged for different time periods; (3) Fluorescent labeling of aged polymer coatings The polymer coating undergoes an aging reaction and undergoes chemical changes to produce different functional groups. According to the different groups produced by the aging of the polymer coating, a specific fluorescent probe molecule corresponding to each group is selected; a dye is selected according to the functional groups that may be produced by the aging of the polymer coating in step (2), and the antique metal is immersed in the fluorescent dye for 30 minutes so that the functional groups produced by aging are stained by the fluorescent probe molecules, and then rinsed with deionized water for 1 minute to wash away the free fluorescent probe molecules, and the stained sample is fixed on a sample stage for confocal three-dimensional fluorescence imaging; (4) Fluorescence imaging and quantitative analysis of cultural relics sealed with polymers The dyed polymer used to seal the cultural relics is observed and imaged using a laser scanning confocal microscope: different lasers are used to excite different probe molecules corresponding to the polymer in step (3), and the emission wavelength range is adjusted to capture the emission wavelength signals of different fluorescent molecules for imaging; the scanning range of the Z axis is appropriately adjusted according to the thickness of the polymer sealing layer; Quantitative information is obtained through the results of three-dimensional imaging for analysis, and the aging sites on the polymer surface and the polymer-artifact interface are studied. The aging behavior at the polymer-artifact interface is explored through analysis and comparison of the depth and volume changes of the fluorescence sites, and the influence of the artifacts at the interface on the aging of the polymer is analyzed; (5) Comparative study of cultural relics sealed with polymer and inactive substrates Select inactive substrates such as quartz wafers and silicon wafers as control samples to replace antique metals, use the same spin coating, aging treatment, fluorescent staining, imaging and quantitative analysis methods to compare the effects of inactive substrates and cultural relics on the polymer aging process, and use fluorescent imaging analysis and other methods to compare the influence of different substrates. For example, use the same method as step (4) to compare the aging points on the polymer upper surface and the interface with the substrate corresponding to different substrates. The aging points on the polymer upper surface corresponding to the inactive substrate and the polymer upper surface corresponding to the antique metal have the same growth trend or little difference. At the same time, if the growth trend of the aging sites on the surface of the inactive substrate is more or larger than the growth sites on the surface of the antique metal, it is possible that the antique metal has an effect on the aging process of the polymer; age the polymer coatings on different substrates for different times and test the infrared spectrum, perform spectrum analysis, calculate the carbonyl index, etc., to compare the effects of different substrates on the polymer aging process, so as to explore and then obtain whether the antique metal accelerates or inhibits the aging process of the polymer protective layer; (6) Study the chemical changes of the cultural relics themselves, and then explore whether the substances produced by the aged polymers will affect the cultural relics themselves (a) The cultural relics or antique metals that have been sealed with polymer coatings are aged for different periods of time, including the case where only the polymer coating is sealed but not aged and the case where it is aged for a period of time. The polymer is then removed with a solvent, and the newly exposed surface of the cultural relics is subjected to X-ray electron energy spectrum and metal electrochemical tests. (b) The cultural relics or antique metals that are not sealed with polymer coatings are aged under the same conditions as step (a), and then combined with step (a), it is explored whether the substances produced by the aged polymer will have an impact on the cultural relics themselves.

2. The method according to claim 1, characterized in that Step (6) Taking X-ray electron spectroscopy analysis as an example, the analysis of iron cultural relics is carried out by analyzing the ratio of the active substances newly generated by aging to the inactive substances in the cultural relics: Fe 3+ (Represents active substances newly generated due to aging) / Fe 0 (representing the inactive substance content of the cultural relic itself) to quantitatively analyze the impact of aging polymer on the cultural relic itself. 3+ / Fe 0 The ratio of Fe to unsealed polymer-coated cultural relics after aging under the same conditions 3+ / Fe 0 The ratio of > unaged cultural relics Fe 3+ / Fe 0 The ratio of polymer to cultural relics shows that aging of polymer has an impact on the cultural relics and caused damage to them.

3. Application of the method described in claim 1 or 2, by studying the effects of different polymer materials on the body of cultural relics, screening out polymer protective materials that cause less damage to cultural relics and can safely protect cultural relics, thereby achieving long-term and safe protection of cultural relics.

4. In the application of the method described in claim 1 or 2, the influence of the cultural relic body on the polymer directly determines the protective effect and service life of the polymer; exploring the influence of the cultural relic body on the polymer is conducive to understanding the service life of the polymer, replacing or repairing the polymer protective material before it fails, and avoiding the cultural relic from being damaged due to the failure of the protective material causing it to lose its protective effect on the cultural relic body.